Scaling Power and Performance via Processor Composability - Govindan, Madhu Saravana Sibi; , Behnam Robatmili; Li, Dong; , Bertrand A. Maher; Smith, Aaron; , Stephen W. Keckler; Burger, Doug (IEEE Transactions on Computers, 2014)
Power dissipation trends are leading high-performance processors to a regime in which all chip elements cannot be operated simultaneously at maximum frequency. Consequently, energy-efficiency will increase even more in importance, and performance must be achieved within strict power budgets. Current designs employ techniques such as dynamic voltage and frequency scaling (DVFS) to provide power-performance tradeoffs for both single and multi-threaded workloads. In power-dominated regimes, processors will be run at or near the minimum voltage. Frequency can be reduced to save power, but there is no scaling strategy for increasing performance with high energy-efficiency if the processor is operating at its maximum frequency (and minimum voltage). In this paper, we evaluate the energy-efficiency of processor composability—dynamically aggregating small energy-efficient physical cores into larger logical processors—as a method of scaling single-threaded performance up and down, comparing composability to the energy-efficiency of voltage and frequency scaling. We measure the power breakdowns of the baseline composable microarchitecture (the TFlex microarchitecture, based on an EDGE ISA) and compare the energy-efficiency and performance to one processor designed for power-efficiency (XScale) and another designed for high-performance (a variant of the Power-4) using normalized power models for as fair a comparison as possible. The study shows that composing multiple dual-issue cores (up to eight) provides performance scaling that is as energy-efficient as frequency scaling in a balanced microarchitecture, and is considerably more efficient than scaling the voltage to achieve additional performance once the maximum frequency at the minimum voltage is attained.